Relationship Between Knowledge Level, Distance from Home and Type of Transportation with Length of Arrival of Stroke Patients in The Emergency Group of Prof. Dr. Margono Soekarjo Purwokerto Hospital - Prayitno, Arif Munandar; Fitriana, Nurul Fatwati (Proceedings Series on Health & Medical Sciences, 2025)
Background: Stroke is a medical emergency condition (stroke is brain attack), the faster the diagnosis is made, the faster the treatment. The low level of public understanding of strokes results in families delaying taking stroke patients to health facilities. Method: This study uses a descriptive correlative study with a cross-sectional approach. The sample in this study was 41 respondents with stroke attacks who came to the Emergency Room of Prof. Dr. Margono Soekarjo Hospital with the research instrument used being a questionnaire. Results: Respondent characteristics were female 51.2%, college education level (PT) 46.5%, private job type 56.0%, and respondents aged 41 years to 50 years 51.4%. Respondents with good knowledge 48.8%, distance from home to RSMS ER <10 KM (close) 48.8%. The type of transportation used was a private car 70.7%, then the length of arrival of stroke patients to the RSMS ER according to the golden time is 58.5%. Family knowledge about stroke is good with the length of the arrival of stroke patients at the RSMS ER <4.5 hours 58.5%, distance from home 1-10 KM with the speed of the family carrying stroke patients <4.5 hours 36.6%, and the type of private car transportation with the speed of the family carrying stroke patients <4.5 hours 36.1%. Conclusion: There was a relationship between the level of family knowledge about stroke and the speed of the family taking the stroke patient to the hospital. There is no relationship between the distance from home and the length of time the stroke patient arrives at the RSMS Emergency Room. There is a relationship between the type of transportation and the length of time the stroke patient arrives at the RSMS Emergency Room.